Emerging trends in fisheries and aquaculture - Sakhare, V. B. (Daya &Astral Internatoinal, 2013)
Proceedings of the National Conference on Emerging Trends in Fisheries and Aquaculture, organised by Post Graduate Department of Zoology, Yogeshwari Mahavidyalaya during 27-28 September 2012.